Transitional Materialities and the Performance of JavaScript. - Walker, Nathan (Performance Research, 2013)
The article offers the author's insights offers the author's insights regarding the association between digital writing practice and performance. Among the key topics that were mentioned include propositions of Italian futurist Filippo Thomaso Marinetti, the importance of JavaScript computer code for phonic utterance, and the literary contribution of critic N. Katherine Hayles.